Human Albumin Use in Adults in U.S. Academic Medical Centers - Suarez, Jose I; Martin, Renee H; Hohmann, Samuel F; Calvillo, Eusebia; Bershad, Eric M; Venkatasubba Rao, Chethan P; Georgiadis, Alexandros; Flower, Oliver; Zygun, David; Finfer, Simon (Critical care medicine, 2017)
To determine rates and predictors of albumin administration, and estimated costs in hospitalized adults in the United States. Cohort study of adult patients from the University HealthSystem Consortium database from 2009 to 2013. One hundred twenty academic medical centers and 299 affiliated hospitals. A total of 12,366,264 hospitalization records. Analysis of rates and predictors of albumin administration, and estimated costs. Overall the proportion of admissions during which albumin was administered increased from 6.2% in 2009 to 7.5% in 2013; absolute difference 1.3% (95% CI, 1.30-1.40%; p < 0.0001). The increase was greater in surgical patients from 11.7% in 2009 to 15.1% in 2013; absolute difference 3.4% (95% CI, 3.26-3.46%; p < 0.0001). Albumin use varied geographically being lowest with no increase in hospitals in the North Eastern United States (4.9% in 2009 and 5.3% in 2013) and was more common in bigger (> 750 beds; 5.2% in 2009 and 7.3% in 2013) compared to smaller hospitals (< 250 beds; 4.4% in 2009 to 6.2% in 2013). Factors independently associated with albumin use were appropriate indication for albumin use (odds ratio, 65.220; 95% CI, 62.459-68.103); surgical admission (odds ratio, 7.942; 95% CI, 7.889-7.995); and high severity of illness (odds ratio, 8.933; 95% CI, 8.825-9.042). Total estimated albumin cost significantly increased from $325 million in 2009 to $468 million in 2013; (absolute increase of $233 million), p value less than 0.0001. The proportion of hospitalized adults in the United States receiving albumin has increased, with marked, and currently unexplained, geographic variability and variability by hospital size.